Formulasi Krim Pelembab Kombinasi Ekstrak Lidah Buaya (Aloe vera) dan Ekstrak Kulit Manggis (Garcinia mangostana L.) - Leny Leny; Indra Ginting; Rachel Anastasia R Hutabarat; Suprianto Suprianto; Benni Iskandar (Journal of Islamic Pharmacy, 2022)
Aloe vera contains flavonol compounds, saponins such as kaempeferol, quercetin and merycetin as much as 257.7, 94.80 and 1283.50 mg/kg, respectively. Saponins contained in aloe vera gel are able to clean the dirt from skin. Vitamin E in aloe vera is also able to soften, moisturize and increase smoothness of the skin. Mangosteen peel waste contains higher xanthones  compared to the mangosteen fruit itself. In 100 grams of mangosteen peel, there are 107.76 mg of xanthones which are an extraordinary nutritions for the skin because they act as antioxidants and antiaging. This study aims to formulate a combination of aloe vera flesh extract and mangosteen peel extract into a cream dosage form and observe the effect in moisturizing the skin of volunteers within 3 months of treatment.The research was initiated by making extracts of aloe vera and mangosteen peel by using the maceration method. Then the extract was formulated into cream preparations with varies concentrations of each cream A (0%:20%), cream B (5%:15%), cream C (10%:10%), cream D (15%:5% ), cream E (20%:0%). The preparations were evaluated for their physical characteristics, namely homogeneity test, pH test, organoleptic test, dispersibility test, stability test, irritation test and its effectiveness in moisturizing volunteers skin using a moisture checker.The results showed that the combination extract of aloe vera flesh and mangosteen peel can be formulated in cream preparation that is homogeneous, does not change color, and remains stable in 12 weeks of storage with a pH between 6.0-6.6. The best cream formula in increasing moisture of skin are found in cream with a combination of 15% aloe vera flesh extract with 5% mangosteen peel extract by an uplifting until 92.5%.Lidah buaya atau aloe vera mengandung senyawa flavonol, saponin seperti kaempeferol, quercetin dan merycetin masing-masing sebanyak 257,7, 94,80 dan 1283,50 mg/kg. Kandungan saponin yang terdapat dalam gel lidah buaya dapat membersihkan kotoran dari kulit. Vitamin E pada aloe vera juga mampu melembutkan, melembabkan dan menambah kehalusan kulit. Limbah kulit manggis mengandung xanthone yang lebih tinggi daripada dalam daging buah manggis. Dalam 100 gram kulit manggis terdapat  xanthone sebesar 107,76 mg dan memiliki khasiat yang luar biasa untuk kulit karena berperan sebagai antioksidan dan antiaging. Penelitian ini bertujuan untuk memformulasikan kombinasi ekstrak daging lidah buaya dan ekstrak kulit buah manggis ke dalam bentuk sediaan krim dan mengamati efek kelembaban pada kulit sukarelawan selama 3 bulan perawatan.Penelitian diawali dengan membuat ekstrak lidah buaya dan kulit manggis yang diperoleh dengan menggunakan metode maserasi. Kemudian ekstrak diformulasikan menjadi sediaan krim dengan variasi konsentrasi masing-masing krim A (0%:20%), krim B (5%:15%), krim C (10%:10%), krim D (15%:5%), krim E (20%:0%). Sediaan dievaluasi untuk karakteristik fisiknya yaitu uji homogenitas, uji pH, uji organoleptis, uji daya sebar, uji stabilitas, uji iritasi dan uji kelembaban pada sukarelawan dengan menggunakan moisture checker.Hasil penelitian menunjukkan bahwa ekstrak daging lidah buaya dan kombinasi kulit buah manggis dapat di formulasikan dalam sediaan krim pelembab yang homogen, tidak berubah warna, dan tetap stabil dalam penyimpanan 12 minggu dengan pH 6,0-6,6. Formula krim terbaik yang memberikan efek peningkatan kadar air tertinggi adalah krim dengan kombinasi ekstrak daging lidah buaya 15% dengan ekstrak kulit manggis 5% dengan peningkatan hingga 92,5%.